Optimizing Classroom Management Strategies to Enhance Student Academic Achievement: A Case Study of Rural Primary Education in Indonesia - Yumnatul Khoyriyah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
Classroom management in rural settings often faces multifaceted challenges, ranging from limited resources to socio-economic constraints. While urban education has been extensively studied, there is a scarcity of focused research on how optimized management strategies correlate with academic performance in Indonesian rural primary schools. Objective: This study aims to analyze the implementation of optimized classroom management strategies and their efficacy in enhancing student academic achievement at SDN Siyar Rembang. Methods: Employing a qualitative case study design, data were gathered through in-depth interviews, participant observation, and documentary analysis. The subjects included the school principal, teachers, and students, selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, ensuring trustworthiness through triangulation and thick description. Results: The findings reveal that optimization is achieved through three core pillars: proactive spatial engineering, fluid transition management, and culturally responsive relational pedagogy (based on the Gotong Royong principle). Observations indicated a 30% increase in Academic Learning Time (ALT) when reactive discipline was replaced with proactive "withiness" and non-verbal cues. Conclusion: This study concludes that management precision can offset infrastructural limitations in rural areas. Optimizing the classroom environment creates a psychologically safe and structured ecosystem that directly fosters cognitive engagement and sustainable academic excellence.